Review on pathogenic mechanism of Magnaporthe oryzae and new green prevention and control strategy - LU Xuanjun; SU Zhenzhu; LIU Xiaohong; LIN Fucheng (浙江大学学报. 农业与生命科学版)
Rice blast caused by Magnaporthe oryzae is a worldwide disease, which seriously affects the global rice production. The rapid variation of M. oryzae resulted in a decline in resistant variety screening and pesticide control. Therefore, revealing the pathogenic mechanism of M. oryzae at the molecular level can provide target molecules for rice disease control and new fungicide development. The utilization of endophytic fungi from wild rice to control rice blast provides a new idea for green management. By excavating the resources of wild rice endophytic fungi, identifying functional strains with the activities of promoting growth, immune induction and resistance to adverse conditions, and exploring the interaction mechanism between rice and endophytic fungi, it provides a basic theory for the development of endophytic fungi as new biocontrol agents. This review mainly summarized the novel research results on the pathogenic mechanism of M. oryzae and the functional mechanism of endophytic fungi in rice in recent years, and look forward to the future development direction of a new green prevention and control strategy for M. oryzae.